HUBUNGAN STATUS PARITAS DENGAN KEJADIAN PERSALINAN KETUBAN PECAH DINI DI RSUD dr. SOESELO SLAWI KABUPATEN - Natiqotul Fatkhiyah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Labor with premature ruptur of membranes is high risk to maternal and infant mortality, Which one of the cause  is  multiparity.  the  research’s  goal  is  to  know    The  correlation  between  parity  status  with  premature rupture of membranes, is the parity  status  can caused premature  ruptur of membranes. This research   used discriptive  correlation  method  with  cross  sectional  approach.  The  sampling  technic  by  purposive  random sampling  and  total  sample  are  620  from  1.235  total  population.  The  result  of  research,  amount  of  multiparous  mother  with  premature  ruptur  of  membranes  161  (48.35%)  and  multiparous  mother  without premature  ruptur  of  membranes  171  (51.65%).  Whereas  amount  of    nulliparous  mother  with  premature ruptur  of  membranes  146  (50.87%)  and  nulliparous  mother  without  premature  ruptur  of  membranes  141 (49.13%). After analized by chi square test (X2) and p value with 5 % significance level obtained results X2